Inner ear manifestations in CHARGE: Abnormalities, treatments, animal models, and progress toward treatments in auditory and vestibular structures. Issue 4 (30th October 2017) - Choo, Daniel I.; Tawfik, Kareem O.; Martin, Donna M.; Raphael, Yehoash
Abstract : The inner ear contains the sensory organs for hearing and balance. Both hearing and balance are commonly affected in individuals with CHARGE syndrome (CS), an autosomal dominant condition caused by heterozygous pathogenic variants in the CHD7 gene. Semicircular canal dysplasia or aplasia is the single most prevalent feature in individuals with CHARGE leading to deficient gross motor skills and ambulation. Identification of CHD7 as the major gene affected in CHARGE has enabled acceleration of research in this field. Great progress has been made in understanding the role of CHD7 in the development and function of the inner ear, as well as in related organs such as the middle ear and auditory and vestibular neural pathways. The goals of current research on CHD7 and CS are to (a) improve our understanding of the pathology caused by CHD7 pathogenic variants and (b) to provide better tools for prognosis and treatment. Current studies utilize cells and whole animals, from flies to mammals. The mouse is an excellent model for exploring mechanisms of Chd7 function in the ear, given the evolutionary conservation of ear structure, function, Chd7 expression, and similarity of mutant phenotypes between mice and humans. Newly recognized developmental functions for mouse Chd7 are shedding light on how abnormalities in CHD7 might lead to CS symptoms in humans. Here we review known human inner ear phenotypes associated with CHD7 pathogenic variants and CS, summarize progress toward diagnosis and treatment of inner ear‐related pathologies, and explore new avenues for treatment based on basic science discoveries.